Coastal hazard risk and socio-economic implications of rising sea levels in Pahang and Selangor - Ibrahim, Nur Arifah Najihah; Ariffin, Effi Helmy; Jeofry, Hafeez; Ramli, Muhammad Zahir; Yunus, Kamaruzzaman; Mohamed, Juliana; Miskon, Mohd Fuad (Zibeline International Publishing, 2025)
The rising sea level due to climate change poses a critical threat to Malaysia’s coastal regions, impacting both the physical environment and socio-economic stability. This study assesses the vulnerability of the Pahang and Selangor coastlines by integrating physical and socio-economic data through a combination of qualitative and quantitative methods. A Coastal Vulnerability Index (CVI) was developed using six key parameters: geomorphology, coastal slope, shoreline change rate, mean tidal range, wave height, and rate of sea level rise (SLR). Concurrently, a socio-economic survey was conducted to evaluate community awareness, preparedness, and adaptation strategies toward SLR. The CVI results indicate that 9 out of 14 management units along the Pahang and Selangor coastlines exhibit high to very high vulnerability. The findings reveal that areas with extensive sandy and muddy shorelines, low coastal slopes, and high erosion rates are particularly at risk. Additionally, socio-economic data highlight a concerning lack of awareness and preparedness among coastal communities, despite evidence of shoreline retreat and economic losses. This study underscores the urgent need for targeted coastal management strategies that integrate both physical risk assessments and community-based adaptation measures. The results provide a scientific foundation for policymakers to enhance coastal resilience and sustainable development in Malaysia’s coastal regions.